Adherence and Impact of Medication Regimen Complexity among Geriatric Patients: A Review - Pattani, Danisha; Shirin, Shahana; basheer, Safa; Kasim, Vaheeda Arampulikkal (Indian Journal of Pharmacy Practice)
For medication therapy to be effective, adherence to a prescribed regimen is essential. The adherence of a patient to a treatment regimen can be affected by several factors, complexity of regimen being one of them. The complexity of a medication regimen can be measured by the Medication Regimen Complexity Index (MRCI), a tool developed to assess the complexities of prescribed regimens. Given that geriatric patients often experience chronic and multiple conditions, necessitating a complex pharmacotherapy approach for managing their clinical conditions, monitoring both the complexity and adherence to the medication regimen becomes crucial for achieving better therapeutic outcomes. This approach helps comprehensively understand the relationship between medication regimen complexity and adherence in geriatric patients. Geriatric patients frequently encounter polypharmacy, comorbidities and cognitive impairments, which can complicate their medication regimens. The MRCI helps healthcare providers evaluate these complexities and develop strategies to improve adherence. Simplifying regimens, providing patient education and leveraging technology-based interventions are essential strategies to enhance adherence. Interdisciplinary collaboration among healthcare professionals is vital in addressing these challenges. By combining expertise from various disciplines, comprehensive medication management programs can be created to support patient adherence and optimize treatment regimens. In conclusion, recognizing and managing medication regimen complexities in geriatric care are vital for promoting better health outcomes and improving the quality of life for older adults. The MRCI serves as a valuable tool in this process, aiding in the comprehensive evaluation and management of medication regimens to support adherence and achieve therapeutic goals.
Keywords: Medication Adherence; Medication Regimen Complexity; Medication Regimen Complexity Index (MRCI); Geriatrics; Health outcome; Quality of life